Profil Perilaku Menyimpang Remaja di Jorong Makmur Pasaman Timur - Andre Fernando; Mori Dianto; Besti Nora Dwi Putri (Departement of Mathematics Education, 2023)
This research is entitled Profile of Adolescent Deviant Behavior in Jorong Makmur Pasaman Timur. The background of this research is that there are teenagers who take part in illegal racing, there are teenagers who speed on public streets, there are teenagers who run away from home when fighting with their parents, there are teenagers who skip school, there are teenagers who get drunk, there are teenagers who gamble, there are teenagers returning home at dawn, teenagers making noise at night and teenagers joining in brawls. This study aims to describe the forms of adolescent deviant behavior in Jorong Makmur, East Pasaman seen from: 1) Nonconforming actions. 2) Antisocial acts. 3) Criminal Acts. This type of research was conducted using a quantitative descriptive method. The study population consisted of 39 adolescents selected by total sampling technique with 39 participants. The instrument used is a questionnaire. As for data analysis using interval scores and percentages. The results of research on forms of adolescent deviant behavior in Jorong Makmur, East Pasaman are seen from: 1) Nonconforming actions are in the small category. 2) Antisocial acts are in very little category. 3) Criminal acts are in the very few categories. This research is recommended for adolescents so that they are not easily influenced by deviant behavior by carrying out activities and joining positive communities